2017
DOI: 10.1186/s12940-017-0256-y
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring urban beaches with qPCR vs. culture measures of fecal indicator bacteria: Implications for public notification

Abstract: BackgroundThe United States Environmental Protection Agency has established methods for testing beach water using the rapid quantitative polymerase chain reaction (qPCR) method, as well as “beach action values” so that the results of such testing can be used to make same-day beach management decisions. Despite its numerous advantages over culture-based monitoring approaches, qPCR monitoring has yet to become widely used in the US or elsewhere. Considering qPCR results obtained on a given day as the best availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 28 publications
4
33
0
Order By: Relevance
“…Since its approval by the USEPA in the latest recreational water quality criteria (USEPA, 2012b), the inclusion of qPCR for enterococci detection in routine monitoring is being considered in several states as a rapid method (Dorevitch et al, 2017; Haugland et al, 2014; Kinzelman et al, 2013; USEPA, 2014). The major difference between USEPA Method 1600 and Method 1611 is that the culture‐based method detects only viable enterococci, whereas the qPCR method detects the enterococci DNA within the viable cells, dead cells, or free‐floating DNA (Walters et al, 2009) and also detects the variability in the target enterococcus species (Moore et al, 2008; Ryu et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Since its approval by the USEPA in the latest recreational water quality criteria (USEPA, 2012b), the inclusion of qPCR for enterococci detection in routine monitoring is being considered in several states as a rapid method (Dorevitch et al, 2017; Haugland et al, 2014; Kinzelman et al, 2013; USEPA, 2014). The major difference between USEPA Method 1600 and Method 1611 is that the culture‐based method detects only viable enterococci, whereas the qPCR method detects the enterococci DNA within the viable cells, dead cells, or free‐floating DNA (Walters et al, 2009) and also detects the variability in the target enterococcus species (Moore et al, 2008; Ryu et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The transfer of existing molecular biological tools, such as qPCR, is therefore gaining momentum largely because these methods permit a much more rapid sample processing time (1 -2 hours). Thus, molecular biological tools offer an opportunity to provide a more meaningful statement of microbial risk to water users by providing near-real-time information, and thus enable more informed decisionmaking for water-based activities (Dorevitch et al, 2017). However, our study has suggested that the majority of beach-users don't engage with information on bathing water quality, and so the value of an increase in the speed of reporting microbial water quality to a typical beach-user is limited.…”
Section: Discussionmentioning
confidence: 99%
“…The E. coli culture method with chromogenic substrate is considered by the USEPA to be comparable to membrane filtration for a variety of regulatory purposes [22]. The enterococci quantitative polymerase chain reaction (qPCR) method is used for beach water monitoring, as we have previously described [23]. The simplified rapid coliphage method (EasyPhage, Scientific Methods, Inc., Granger, IN, USA) was compared to EPA Method 1602 using seven serial dilutions of MS2 phage (obtained from Scientific Methods, Inc., Granger, IN, USA).…”
Section: Pou-o 3 Impacts On Fecal Indicators In Wastewater Chicagomentioning
confidence: 99%